Object-oriented electronic document management system - Chee, Nyuk Lin. (2009)
In this current competitive environment, one should be capable of managing its product and process data and define proper business procedure to survive. A proper change control management allows faster response to customer's needs and brings products faster to market. Product Data Management (PDM) is the technology that helps to manage these information and supports change management process. A semi-conductor equipment supplier plans to streamline and automate its current Engineering Change (EC) process and incorporate some PDM features to it.